Desingning User Experience Folklore Book Application with Design Thinking Method (Case Study of Malin Kundang Story) - Nur Handoko*, Thalia Maharani; Persada, Andhika Giri (Riwayat: Educational Journal of History and Humanities, 2023)
Folklore has an important role in children's development because it introduces moral and ethical values that can shape children's character and introduce Indonesian culture and traditions. However, folklore today is less in demand by children. The design of storybook applications that have good reusability is expected to increase children's interest in reading folklore. Therefore, it is necessary to design a folklore book application that uses Design Thinking. The method used in the development of the user experience of the folklore book application "Ceria Story" is the Design Thinking method. There are five stages carried out in this method, namely, empathize, define, ideate, prototype, and testing. The resulting prototype answers four main problems obtained from the empathize, define, and ideate stages. The story that is used as a case study of this application is Malin Kundang folklore because it is one of the popular folklore with a moral message that is suitable for children. The results of testing children's satisfaction with this application get the category "GOOD". Therefore, the folklore book application "Ceria Story" which is designed using the design thinking method can be a solution to the problem of children's lack of interest in folklore.